2012
DOI: 10.1515/znc-2012-3-409
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Helicobacter pylori Activity of the Methanolic Extract of Geum iranicum and its Main Compounds

Abstract: Geum iranicum Khatamsaz, belonging to the Rosaceae family, is an endemic plant of Iran. The methanol extract of the roots of this plant showed signifi cant activity against one of the clinical isolates of Helicobacter pylori which was resistant to metronidazole. The aim of this study was the isolation and evaluation of the major compounds of G. iranicum effective against H. pylori. The compounds were isolated using various chromatographic methods and identifi ed by spectroscopic data (1H and 13C NMR, HMQC, HMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…2 equivalent to 6 × 10 8 cell/mL) and dried at room temperature for 10 min. Afterwards, the sterile blank disc (diameter: 6 mm) were impregnated in the plant extract (500 mg/mL) and placed on the plates, these plates were incubated at 37°C under microaerobic conditions and examined after 3–5 days [22]. Positive control plates included discs impregnated with amoxicillin (1 μg/mL) and the inhibition zone diameters (IZD) were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…2 equivalent to 6 × 10 8 cell/mL) and dried at room temperature for 10 min. Afterwards, the sterile blank disc (diameter: 6 mm) were impregnated in the plant extract (500 mg/mL) and placed on the plates, these plates were incubated at 37°C under microaerobic conditions and examined after 3–5 days [22]. Positive control plates included discs impregnated with amoxicillin (1 μg/mL) and the inhibition zone diameters (IZD) were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…In a research the extract and essential oil of G. kokanicum showed antimicrobial activity and in another study a potent inhibitory effect on matrix metalloproteinase activity was reported from this plant (29,30). In our previous works we reported the presence of terpenoid, steroid, phenylpropanoid, tannin and sugar in the extract and high amount of eugenol in the essential oil of the roots of G. iranicum (4,31).…”
Section: Discussionmentioning
confidence: 92%
“…Few biological and phytochemical studies have been carried out on Geum species in Iran. Our previous work on phytochemical analysis of G. iranicum using column chromatography showed that the root was rich in sugars and sucrose was identified as a major sugar in this plant (4). Sugars as primary messengers in signal transduction regulate many important processes along the whole life cycle of the plant (5).…”
Section: Introductionmentioning
confidence: 99%
“…The mass data of the compounds 1, 2, 3, 6 and 7 have been previously reported [27,28]. The mass of other compounds are followed: Manool (4): EIMS (70eV) m/z : 290 [M] + (8), 272 (40), 204 (20), 257 (58), 189 (28), 137 (100), 121 (48), 95 (67).…”
Section: Resultsmentioning
confidence: 99%